Low methylation of matrix metalloproteinase 1 (MMP1) is associated with preterm labour in Malaysian mothers - Mohamad Zainal, Nurul Hayati; Mohamed Ismail, Nor Azlin; M. Mokhtar, Norfilza (Penerbit Universiti Kebangsaan Malaysia, 2022)
Preterm births comprise 10.6% of livebirths worldwide and account for 35% of deaths among newborn babies. Understanding DNA methylation may offer basic knowledge in the understanding of pathogenesis of preterm labour. The study was undertaken to determine DNA methylation of matrix metalloproteinase 1 (MMP1) promoter in term and preterm labour using methylation-specific polymerase chain reaction (MSP). Thirty maternal venous blood samples (n=15 each) of term and preterm labour was subjected to bisulfite treatment prior to MSP. This result was then validated using DNA sequencing. Evaluation of the sequencing results by CpG islands analysis was performed using the ClustalW and SPSS software. Primers for MMP1 were located between -1226 and -1378 upstream from the transcription start site (TSS) that consisted five CpG islands. Preterm labour group had significantly lower methylated CpG islands with 39 out of total 75 (52%) compared to the term labour that has 49 out of 75 methylated CpG islands (65.33%) (t=0.694, p<0.05). Methylation occurred in 4 out of 5 methylated CpG islands in the MMP1 promoter where it only involved 2 preterm samples (13.33%) and 7 term samples (46.47%). This data suggested there were significant lower percentage of methylated MMP1 in preterm labour. Higher percentage of methylated MMP1 as observed in the term labour, will probably reduce the expression of MMP1, thus maintaining fibrillar collagen strength on the amniotic membrane and subsequently maintain the pregnancy till term. In conclusion, preterm labour has higher percentage of methylated CpG compared with term labour in MMP1 gene.